Biomimetic Models to Investigate Membrane Biophysics Affecting Lipid–Protein Interaction - Sarkis, Joe; Vié, Véronique (Frontiers in Bioengineering and Biotechnology, 2020)
Biological membranes are highly dynamic in their ability to orchestrate vital mechanisms including cellular protection, organelle compartmentalization, cellular biomechanics, nutrient transport, molecular/enzymatic recognition, and membrane fusion. Controlling lipid composition of different membranes allows cells to regulate their membrane characteristics, thus modifying their physical properties to permit specific protein interactions and drive structural function (membrane deformation facilitates vesicle budding and fusion) and signal transduction. Yet, how lipids control protein structure and function is still poorly understood and needs systematic investigation. In this review, we explore different in vitro membrane models and summarize our current understanding of the interplay between membrane biophysical properties and lipid-protein interaction, taken as example few proteins involved in muscular activity (dystrophin), digestion and Legionella pneumophila effector protein DrrA. The monolayer model with its movable barriers aims to mimic any membrane deformation while surface pressure modulation imitates lipid packing and membrane curvature changes. It is frequently used to investigate peripheral protein binding to the lipid headgroups. Examples of how lipid lateral pressure modifies protein interaction and organization within the membrane are presented using various biophysical techniques. Interestingly, the shear elasticity and surface viscosity of the monolayer will increase upon specific protein(s) binding, supporting the importance of such mechanical link for membrane stability. The lipid bilayer models such as vesicles are not only used to investigate direct protein binding based on the lipid nature, but more importantly to assess how local membrane curvature (vesicles with different size) influence the binding properties of a protein. Also, supported lipid bilayer model has been used widely to characterize diffusion law of lipids within the bilayer and/or protein/biomolecule binding and diffusion on the membrane. These membrane models continue to elucidate important advances regarding the dynamic properties harmonizing lipid-protein interaction.